Bra.Di.P.O. and P.I.G.R.O.: Innovative Devices for Motor Learning Programs. (10th March 2014) - Belforte, Guido; Eula, Gabriella; Sirolli, Silvia; Bois, Paolo; Geda, Elisabetta; D'Agata, Federico; Cauda, Franco; Duca, Sergio; Zettin, Marina; Virgilio, Roberta; Geminiani, Giuliano; Sacco, Katiuscia
Abstract : Two mechatronics prototypes, useful for robotic neurotreatments and new clinical trainings, are here presented. P.I.G.R.O. (pneumatic interactive gait rehabilitation orthosis) is an active exoskeleton with an electropneumatic control. It imposes movements on lower limbs in order to produce in the patient's brain proper motor cortex activation. Bra.Di.P.O. (brain discovery pneumatic orthosis) is an MR-compatible device, designed to improve fMRI (functional magnetic resonance imaging) analysis. The two devices are presented together because both are involved in the study of new robotic treatments of patients affected by ictus or brain stroke or in some motor learning experimental investigations carried out on healthy subjects.